2012
DOI: 10.4997/jrcpe.2012.403
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriateness of fresh frozen plasma for abnormal coagulation tests

Abstract: Background:There is increasing evidence to suggest that the use of fresh frozen plasma (FFP) as a prophylaxis to bleeding is ineffective. However, a high proportion of FFP transfusions still occur in non-bleeding patients despite the high risk of adverse events. The aim of the study was to assess compliance with current prophylactic FFP guidelines at a large tertiary centre. Methods: Data were collected retrospectively over a 16-month period from May 2010 to August 2011. Information collected included patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This likely reflects the high level of awareness and compliance with guidelines among the treating physicians on the potential benefits of utilizing the currently available objective laboratory tests for monitoring FFP therapy. Similar popularity in the use of coagulation tests was also noted in some earlier published audits,8, 11, 12, 18, 42 but was far less popular in others 39 . The disagreements surrounding the use of coagulation testing, when resorting to FFP transfusion, underscores the need for good-quality randomized controlled trials to confirm, or otherwise, the benefit of coagulation tests, particularly the PT and APTT, to support the prophylactic infusion of FFP and also to validate the use of the new global tests of haemostasis, such as thromboelastography and the thrombin generation test, as reliable markers of in vivo coagulation 40, 43, 44…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This likely reflects the high level of awareness and compliance with guidelines among the treating physicians on the potential benefits of utilizing the currently available objective laboratory tests for monitoring FFP therapy. Similar popularity in the use of coagulation tests was also noted in some earlier published audits,8, 11, 12, 18, 42 but was far less popular in others 39 . The disagreements surrounding the use of coagulation testing, when resorting to FFP transfusion, underscores the need for good-quality randomized controlled trials to confirm, or otherwise, the benefit of coagulation tests, particularly the PT and APTT, to support the prophylactic infusion of FFP and also to validate the use of the new global tests of haemostasis, such as thromboelastography and the thrombin generation test, as reliable markers of in vivo coagulation 40, 43, 44…”
Section: Discussionsupporting
confidence: 66%
“…In the second part of this audit, we sought to find out how frequently physicians resort to using coagulation tests, particularly the PT and the APTT, before and after FFP infusion, as a monitor of the haemostatic status of the patient before infusion, and also as a guide of its efficacy; the use of the PT and APTT has been stated in the guidelines of the BCSH, 16 the WHO guidelines, 37 the CAP, 18 the American Red Cross and the AABB 38 . The PT and the APTT are currently the most popular indicators of coagulation that are used by clinicians; newer overall tests of haemostasis, such as thromboelastography and the thrombin generation test are still awaiting validation 39, 40. On the other hand, the INR, which was originally devised as a monitor of warfarin therapy, has not gained popularity in relation to the monitoring of FFP transfusion, but it is still being used for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…57 -59 Although the time to test results could be sped up by the use of point-of-care devices for measuring PT/INR, there is a high variability in reported results and thus they may not be useful for identification or exclusion of patients with coagulopathy after trauma. 8 60 Notably, transfusion of FFP without clear indications is performed frequently in the medical community 56 61 and people 62 It should be noted that due to changes of modern bleeding management seen particularly in Europe, for example, PCC may be used increasingly instead of FFP to treat prolonged SLT results, which could lead to serious side-effects and high costs if the use was not justified.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple audits of transfusable plasma utilization have shown that over 30% of the time, plasma is transfused inappropriately, typically in efforts to alter a mildly elevated INR and to nonbleeding patients [101104]. Although most studies of plasma quality end with an exhortation to trialists to obtain better RCT data, it is likely that improvements in plasma utilization could be achieved more readily by diminishing inappropriate transfusion of plasma.…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 99%